The Secondary Education Students’ and Teachers’ Perspectives on EMI - Dian Asmi Setoningsih (English Learning Innovation (englie), 2022)
English-medium instruction (EMI) has become popular and developed as a growing global phenomenon nowadays in International secondary education in Indonesia. By comparison to this phenomenon's rapid growth, the EMI has not indicated immediate effectiveness in its application, in particular. The purpose of this research was to investigate the perspectives of students and teachers of the implementation of EMI at an Indonesian International school called Thursina IIBS Malang and to suggest ways to maximize the advantages of the policy while decreasing its disadvantages. To examine in-depth views and experience of the policy, structured interviews were conducted with 8th graders and academic teachers who were chosen purposively. Focus group discussion (FGD) was then employed to triangulate the data. The interview and FGD results showed that both students and teachers demonstrated strong acceptance of the policy because EMI could facilitate the teaching and learning process better and improve their English skills. However, in the EFL context, it was inevitably difficult to use English fully in the classroom where EMI naturally should be implemented fully in no other languages than English. Therefore, this study is expected to provide suggestions from the perspectives of EFL practitioners to maximize the benefit of the EMI policy in an EFL context.